2018
DOI: 10.29252/jafm.11.04.28397
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of an Oxygen-Blown Bubbling Fluidized Bed Gasifier using the Computational Particle-Fluid Dynamics (CPFD) Approach

Abstract: Fluidized beds are conventional components of many industrial processes, such as coal gasification for energy generation and syngas production. Numerical simulations help to properly design and understand the complex multiphase flows occurring in these reactors. Two modeling approaches are usually adopted to simulate multiphase flows: the two fluids Eulerian-Eulerian model and the continuous/discrete Eulerian-Lagrangian model. Since fluidized beds account for an extremely large number of particles, tracking ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The increased ξ value corresponds to an elevated flow rate of the injected biogas, resulting in a lower local excess air coefficient near the biogas nozzles. This limits the air available for coke burning, thereby reducing unburned coke reaching the SOFA region. , Consequently, the NO emission concentration decreases with the increased cocombustion ratio ξ across all types of biogases. The fact that the NO emission is inversely proportional to the cocombustion ratio is consistent with the findings of Yang’s work. , …”
Section: Resultsmentioning
confidence: 99%
“…The increased ξ value corresponds to an elevated flow rate of the injected biogas, resulting in a lower local excess air coefficient near the biogas nozzles. This limits the air available for coke burning, thereby reducing unburned coke reaching the SOFA region. , Consequently, the NO emission concentration decreases with the increased cocombustion ratio ξ across all types of biogases. The fact that the NO emission is inversely proportional to the cocombustion ratio is consistent with the findings of Yang’s work. , …”
Section: Resultsmentioning
confidence: 99%
“…The results supported that the two-dimensional CPFD model could effectively predict the flow pattern of particles near the feed zone. Nardo et al (2018) found that CPFD model could assure a more effective contact of gas with solid bed and a good bubbling fluidization mechanism, and the prediction of the outlet gas composition was satisfactory. Raheem et al (2019) conducted experimental and CPFD numerical research on CFB combustor under cold flow conditions.…”
Section: Introductionmentioning
confidence: 90%
“…The gas-liquid two-phase flow behaviors are extremely complex in a cyclone separator. The structural size plays an important role on the flow field and the separation performance of the cyclone (Gao et al 2020;Nardo et al 2018). Computational Fluid Dynamics (CFD) is an effective technique to explore the complex flow field in a cyclone, and predict the droplet behavior and performance.…”
Section: Introductionmentioning
confidence: 99%